Comparison of prognostic value of epicardial blood flow and early ST-segment resolution after primary coronary angioplasty. ANIN--Myocardial Infarction Registry - Kalińczuk, Łukasz; Przyłuski, Jakub; Karcz, Maciej; Petryka, Joanna; Kaczmarska, Edyta; Bekta, Paweł; Kepka, Cezary; Kruk, Mariusz; Pregowski, Jerzy; Kadziela, Jacek; Deptuch, Tomasz; Skwarek, Mirosław; et al. (Kardiologia polska (1957), 2007)
TIMI scale is commonly used for angiographic assessment of reperfusion effectiveness and early risk stratification in patients treated with primary angioplasty for ST-elevation myocardial infarction (STEMI). Since ST-resolution analysis allows a noninvasive insight into the reperfusion status at the myocardial tissue level, it may be a better predictor of outcome after primary angioplasty. To compare the prognostic value of the reperfusion effectiveness evaluation based on either the epicardial blood flow assessment according to the TIMI scale, or ST-segment resolution analysis in patients treated with primary coronary angioplasty for STEMI. 324 consecutive patients treated within 12 hours from the pain onset were studied. Based on the analysis of maximal ST-segment elevation/depression identified in a single ECG lead recorded after the procedure (maxSTE), patients were classified into groups of high versus medium/low risk. Independently, distinguished were groups with restored normal (TIMI 3) and abnormal (TIMI 0-2) final blood flow in infarct related artery. The 30-day and one-year mortality rates were higher in the high-risk maxSTE group (25% of all patients) than in the other patients (14.8% vs. 2.5%, p<0.001 and 18.5% vs. 5.4%, p<0.001 respectively). In subjects (82%) with restored TIMI grade 3 blood flow, mortality at one-month and one-year was lower than in the group with abnormal final blood flow (3.1% vs. 15.6%, p=0.001 and 6.2% vs. 18.8%, p=0.005). Comparison in multivariate analysis revealed that maxSTE stratification but not final TIMI grade assessment remained an independent predictor of both, 30-day and one-year mortality (high vs. medium/low-risk category; OR 5.3, 95% CI 1.6-16.7, p=0.005, and OR 3.3, 95% CI 1.4-7.8, p=0.007, respectively). Furthermore, maxSTE proved to stratify the risk of death even in subgroup of patients with restored normal blood flow (OR 6.2, 95% CI 1.4-27.8, p=0.016, and OR 3.0, 95% CI 1.1-8.7, p=0.039, respectively). Analysis of extent of maximal ST-segment elevation or depression identified in a single ECG lead after primary coronary angioplasty allows better prognosis of subsequent 30-day and one-year mortality than the assessment of final epicardial blood flow, stratifying risk of death even in a subgroup of patients with restored normal blood flow.